STUDY OF THE ANXIOLYTIC ACTIVITY OF ETHANOLIC EXTRACT OF ROOT OF ACORUS CALAMUS IN ALBINO MICE - KAUSHIK, SHIPRA; KAUSHIK, SHOBHIT (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Anxiety is classified as a form of sub-acute or chronic fear. Root of Acorus calamus has been traditionally used as an anxiolytic. The aim of the study is to assess the anxiolytic activity of ethanolic extract of A. calamus (EEAC) by elevated plus-maze test on Albino mice. Methods: Albino mice of either sex were taken and divided into five groups, each consisting of 5 mice. One group was used as control, one as standard (diazepam), and three as test groups treated with 100, 200, and 400 mg/kg of EEAC. The drugs, that is, 10 ml/kg of normal saline for control, diazepam 2 mg/kg (standard), and 100, 200, and 400 mg/kg EEAC (test groups) were injected intraperitoneally (i.p.), 30 min before placing them in the center of the maze. The preferences of the animal to open/enclosed arm, average time spent in open arm, and numbers of entries in open arm were compared in each group. Data were statistically analyzed by one-way analysis of variance followed by multiple Dunnett’s test. Results: The number of entries in open arm and the average time spent in the open arm by the mice is increased by EEAC in a dose-dependent manner. Conclusion: EEAC has anxiolytic activity.